Quantifying Growth Rates Using Growth Checks in Colonial Organisms: A Case Study on Erect Bryozoans From the Southern Ocean - Marcus M. Key; Abigail M. Smith; Madelaine S. McDowell; Ian S. Dixon‐Anderson (Marine Ecology, 2025)
As environmental change accelerates, marine invertebrate growth rates may change in response to a variable environment. Some colonial invertebrates manifest annual growth checks in their skeletons, as somatic growth slows or stops in winter. Here we describe a morphometric measurement methodology to quantify growth rates using annual growth checks visible on X‐rays and SEM images. We tested our method on three rigid erect perennial cheilostome bryozoan colonies belonging to the marine species Cellarinella nutti , Melicerita chathamensis , and M. obliqua . They were collected from 150 to 500 m water depth and from 48° S to 78° S latitude. The growth checks in all three species were identified visually in X‐ray images. We trialed the use of morphometric data from composite SEM images, including measures of branch width, number of autozooids across branch, autozooid length, and autozooid width, but they did not significantly correlate with growth checks from the X‐ray images in all species. In the two polar species, the winter growth checks were associated with slightly longer autozooids. Assuming that growth checks were annual, growth rates were calculated to be from 2.81 to 3.54 mm/year, decreasing over time. Our hypothesis is that a combination of X‐ray imaging and morphometric data collection on composite SEM images shows promise for application to other bryozoan species and marine invertebrates from temperate/polar regions.

Cheilostome bryozoan epibiosis on brachyuran crabs in the Paratethys Sea during the late Badenian (middle Miocene) - Marcus M. Key; Matúš Hyžný; Kamil Zágoršek; Alfréd Dulai (PalZ, 2024)
This study quantifies the prevalence of a rarely documented occurrence of bryozoans encrusting fossil brachyuran crabs. Over 500 crab fossils were examined from the reef facies of the Rákos Limestone Member of the Leitha Limestone Formation in the quarry at Diósd, Hungary. They were deposited in the upper part of the regional Badenian stage (i.e., lower part of the international Serravallian stage) of the middle Miocene. Nine bryozoan colonies were found encrusting five dorsal carapaces of three different crab species: Panopeus wronai , Dromia neogenica , and Cancer styriacus . The bryozoans were restricted to the exterior surface of the preserved carapaces of the host crabs, so the epibiosis was most likely syn-vivo . The prevalence was calculated at 1%. The bryozoans were all cheilostome gymnolaemates identified as a cribrilinid, a calloporid, Onychocella ? sp., and two indeterminate membraniporiform species. The low prevalence of bryozoan-encrusted crabs is consistent with other fossil-based bryozoan-crab studies but much lower than similar studies in today’s faunas. This discrepancy was attributed to both colony spalling-induced preservational bias and differences in carapace size. The bryozoan-crab symbiosis was described as phoretic hitchhiking.

Rare report of bryozoan fouling of rock lobsters ( Jasus edwardsii : Decapoda: Palinuridae) from the North Island of New Zealand - Marcus M. Key; Abigail M. Smith; Benn Hanns; Pamela Kane‐Sanderson (New Zealand Journal of Marine and Freshwater Research, 2023)
Bryozoan epibiosis on lobster hosts is rarely reported. Here we document bryozoan fouling of the spiny rock lobster Jasus edwardsii from the Hauraki Gulf, North Island of New Zealand. The 92 lobsters in this study came from the Cape Rodney‐Okakari Point Marine Reserve. The lobsters were measured for size and weight, sexed, scanned for epibionts, and photographed. Forty‐two per cent of the lobsters were fouled by epibionts, but only 9% by bryozoans, and they were all males. The bryozoans were all cheilostome gymnolaemates. Only erect colonies were found on the dorsal carapace, and only encrusting colonies were found on the ventral surface. Two of the erect colonies were found in gaping exposed wounds through the exterior wall into the branchial chamber. In addition to host wounds, differences in frequency and location of fouling bryozoan colonies were also attributed to time since last moult and grooming. This epibiosis is interpreted as more of a one‐sided commensal symbiotic relationship, perhaps best described as phoretic (i.e. hitchhiking relationship).

Trepostome bryozoans buck the trend and ignore calcite-aragonite seas - Marcus M. Key; Patrick N. Wyse Jackson; Catherine M. Reid (Palaeobiodiversity and Palaeoenvironments, 2022)
Trepostome bryozoan skeletalisation did not passively respond to changes in seawater chemistry associated with calcite-aragonite seas. According to Stanley and others, trepostome bryozoans were passive hypercalcifiers. However, if this was the case, we would expect their degree of calcitic colony calcification to have decreased across the Calcite I Sea to the Aragonite II Sea at its transition in the Middle Mississippian. Data from the type species of all 184 trepostome genera from the Early Ordovician to the Late Triassic were utilised to calculate the Bryozoan Skeletal Index (BSI) as a proxy for the degree of calcification. BSI values and genus-level diversity did not decrease across the transition from the Calcite I Sea to the Aragonite II Sea. Nor were there any changes in the number of genus originations and extinctions. This suggests that trepostome bryozoans were not passive hypercalcifiers but active biomineralisers that controlled the mineralogy and robustness of their skeletons regardless of changes in seawater chemistry.

An Historical Geoarchaeological Approach to Sourcing an Eighteenth Century Building Stone: Use of Aquia Creek Sandstone in Christ Church, Lancaster County, VA, USA - Marcus M. Key; Spencer B. Lieber; Robert J. Teagle (Geoheritage, 2020)

Paleoenvironmental reconstruction of the Early to Middle Miocene Central Paratethys using stable isotopes from bryozoan skeletons - Marcus M. Key; Kamil Zágoršek; William P. Patterson (International Journal of Earth Sciences, 2013)

Bryozoan colonization of the marine isopod Glyptonotus antarcticus at Signy Island, Antarctica - Marcus M. Key Jr; David K. A. Barnes (Polar Biology, 1999)

Primary irritant contact dermatitis from synthetic pyrethroid insecticide exposure - Stephen A. Flannigan; Stephen B. Tucker; Marcus M. Key; Charles E. Ross; Edward J. Fairchild; Barbara A. Grimes; Ronald B. Harrist (Archives of Toxicology, 1985)